English Language Arts schemes of work: Year Two, Terms 2 and 3 - Belize. Ministry of Education. Curriculum Development Unit (Ministry of Education, 1991)
This booklet contains the final set of schemes for the two year programme of English Language Arts teaching in Belize. The cognitive objectives, content, activities, run-through activities, evaluation and references are provided for each theme.
Keywords: Secondary school curriculum